Mental model and scientific reasoning ability of chemistry education students during Covid-19 Pandemic online learning - Supriadi Supriadi; Wildan Wildan; Aliefman Hakim; Jeckson Siahaan; Mukhtar Haris; Sunniarti Ariani (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
This study aims to find: (1) the development of students' scientific reasoning abilities; (2) mental models developed by students in understanding the concept of dissolving weak acids and weak bases; and (3) the relationship between scientific reasoning abilities and mental models. The research approach is a descriptive study. The research subjects were 38 first-year students of the Chemical Education Study Program, Faculty of Teacher Training and Education, The University of Mataram. The research data collected were scientific reasoning ability data and student mental model data on the concept of dissolving weak acids and weak bases. Students' scientific reasoning ability was measured using the revised Classroom Test of Scientific Reasoning (CTSR) instrument in 2000, developed by Lawson and translated into Indonesian. The translation test has a reliability coefficient, calculated by the KR-20 formula, of 0.74. Identification of mental models using written tests and interviews. The content validity of the mental model test instruments is 94.2%. The data obtained were analyzed descriptively. The identification of mental models is made by using a constant comparative technique. The results showed a delay in developing students' scientific reasoning abilities compared to the criteria set by Lawson. Most of the students developed initial mental models in understanding dissolving weak acids and bases. In addition, the higher the student's scientific reasoning ability, the mental model developed tends to approach the scientific mental model.